Using Augmented Reality and Geographic Information System to Improve Building Site Selection - Humam Khairy, Alaa; Taha Abdullah, Nahidh (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
When designing, or developing any city, whatever its size, the biggest problem facing the architect is choosing the best location for public facilities within the urban fabric. To this day, no scientific computational method has been established to be used to find the best site from an architectural perspective for a public service buildings that takes advantage of new digital technologies. The objective of this paper is to formulate a methodology that takes advantage of new digital technologies and standardizes a set of specific measurable metrics in form of 3D matrix. This can be achieved by formulating a criteria for measuring the necessary factors required to distinguish between a set of candidate sites and find best suitable location for the construction of a specific building, based on Augmented Reality (AR) technology and benefiting from the data provided by the Geographic Information System (GIS) and trying to answer important questions: Are Augmented Reality (AR) technology an appropriate methodology to correctly find suitable location for newly constructed buildings? Will it really enhance the architect's experience and improve his performance? It appears that the use of digital technology in any applied field improves the accuracy and task completion time of the result, is this also true for the problem under discussion? Accordingly, setting up clear and unified standard measuring criteria agreed upon all architect and urban planners as these measures will have tangible values, , thus enriching the experience of both the client and the architect.